Efficacy of a No-Team Version of the Good Behavior Game in High School Classrooms. (July 2020) - Ford, W. Blake; Radley, Keith C.; Tingstrom, Daniel H.; Dufrene, Brad A.
Disruptive behavior (DB) negatively affects the learning process in various ways, interfering with the educational process of individual students, the teacher, and/or the class as a whole. Group contingency interventions, such as the Good Behavior Game (GBG), are often used classwide to provide teachers with evidence-based management strategies while improving student behavior. In the present study, we evaluated the effects of a streamlined, no-teams version of the GBG in general education high school classrooms. Although the GBG has been assessed in a variety of settings, it has limited empirical evidence for use with secondary-level students, indicating a significant need for such an evaluation. The effects of the intervention were determined with an A/B/A/B single-case withdrawal design in three classrooms (ninth, 10th, and 11th grades). The results of the study indicated that the no-team version of the GBG was effective at reducing levels of DB and increasing levels of academic engagement in each classroom. Furthermore, the intervention procedures were found to be acceptable to each of the teachers, indicating that the streamlined version of the GBG is an efficient and effective strategy for improving student behavior in high school classrooms.